CHEMICAL COMPOSITION OF FRESH DAGGERTOOTH PIKE CONGER FISH IS (Congresox talabon). - Febrina Tumangger; Andarini Diharmi; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTDaggertooth pike conger fish is a type of demersal fish that can live up to a depth of 100 m in river estuaries. The crayfish can grow up to 200 cm long but the average length is 100-150 cm. This study propose to determine the proximate composition of daggertooth pike conger fish (Congresox talabon). The research method used is experimental. The analysis parameters consisted of moisture content, ash, fat and protein (proximate) content. The results showed that the daggertooth pike conger fish had moisture content, ash, fat, and protein content of 78.52%, 1.64%, 1.50% and 18.18%, respectively. The highest chemical composition in daggertooth pike conger fish is moisture content (78.52%) and the lowest is fat (1.5%). Key Words: Daggertooth pike conger fish; chemical composition; moisture content; fat